Unemployment - Turner, Graham; Brooman, F.S.; British Broadcasting Corporation. Television Service (Milton Keynes : Open University, 1976)
Discusses about the unemployment
Converted into VHS 1/2 in.
Title from title screen
Executive producer, Michael Philps ; film editor, Ron De Mattos
Keywords: Unemployment; Employment